“Find One of Your Own Kind”: Auto-ethnography and my Aboriginal Women Ancestors - Dowling, Carol Susan (Curtin University, 2017)
This thesis is an exploration by Badimaya women in my family to interrogate constructions of identity as a decolonising process and generates an account of survival against colonial oppression. The common thread uniting these different strands was my own perspectives, or auto-ethnography which used family stories as strong foundations for contemporary manifestations of a living, continuous indigenous culture. I was able to explore rich, deep and revealing content that documented a counter-colonial history in Australia.